Physical assessment skills practised among critical care nurses in a selected government hospital in Malaysia - Rosli, Syeril Nadia (2022)
Physical assessment (PA) skills are a systematic use of inspection, palpation, percussion, and auscultation techniques. PA is vital in clinical decision-making, enabling nurses to recognise and respond to patients’ clinical changes. Understanding the extent of skills used and the barriers nurses experience when performing PA are crucial. The PA skills practised in Malaysia, particularly among critical care nurses, have little corroboration. This study aimed to identify the PA skills practised by critical care nurses, the perceived barriers and associated factors. This study used a cross-sectional study design with open-ended questions, with approval from the National Medical Research Register. Using a purposive sampling strategy, 133 critical care nurses working in the Medical-Surgical Intensive Care Unit (MSICU), Cardiothoracic ICU (CICU) and Neuro High Dependency Unit (Neuro HDU) at Hospital Sultanah Aminah Johor Bahru were recruited from November 2019 to January 2020. Before recruitment, nurses were screened for eligibility and informed of the study’s objectives and voluntary participation. A six-point Likert scale of 40-item PA skills and a five-point Likert scale of 38-item barriers perceived by nurses were investigated, together with open-ended questions. The survey was adapted from a prior Delphi study. Data were explored and analysed descriptively and inferentially using IBM SPSS version 25 for the Mann-Whitney U test, Kruskal-Wallis test, and the Spearman Correlation test. Qualitative data were reviewed and coded manually into categories before content analysis. The response rate was 88.2%. Most of the nurses worked in MSICU, female and diploma holders. Only 34% of nurses had a post-basic certification. Most of them had less than ten years of experience. The majority of nurses performed 32 of the 40 skills regularly (80%), five skills occasionally (12.5%) and three skills rarely (7.5%). 86% of nurses performed PA skills upon patient admission. The routine skills were vital signs monitoring and PA of neurological, integumentary, nutritional, musculoskeletal, urinary, cardiovascular and respiratory systems. The remaining body system was gastrointestinal. About 20% of nurses did not measure respiratory rate regularly. MSICU nurses (U = 1129, p < 0.001) and nurses with more than ten years of experience (H (2) = 9.60, p = 0.008) performed more PA skills than other groups. Five subscales of barriers, namely “lack of confidence” (r = -0.25), “reliance on others and on technologies” (r = -0.24), “lack of time and interruptions” (r = -0.24), “lack of nursing role models” (r = -0.23) and “lack of influence on patient care” (r = -0.20), significantly affected the nurses’ PA skills. Other factors affecting PA skills included having good knowledge and awareness about PA skills, less paperwork and workload, time management, equipment issues, superiors' encouragement, good role models, and a monitoring system for PA skills. Continuing nursing education, participation in relevant courses, and standardised forms to record PA would improve their skills. The critical care nurses’ PA skills needed improvement. Their backgrounds and perceived barriers influenced their PA skills. Nursing management should pay greater attention to the survey’s concerns about improving PA skills, particularly in critical care settings.